Изучение эффективности микроволновой обработки материалов растительного происхождения - Бошкова, Ирина Леонидовна; Волгушева, Наталья Викторовна (НТУ "ХПИ", 2018)
Изучаются эффекты действия микроволнового электромагнитного поля на материалы растительного происхождения (семена, стебли травянистых растений). Показано, что в определенных режимах обработки наблюдается распушение целлюлозных волокон, что объясняется развитием больших градиентов давлений в материале. Приведены данные по оптимальным режимным параметрам для биостимуляции семян, стерилизации соломы при подготовке субстрата и экстрагированию веществ из некоторых видов растений. Проведена оценка энергетической эффективности методов микроволновой обработки на основе данных по КПД микроволновой камеры с загружаемым материалом. Определены условия достижения максимального КПД рабочей камеры при ее загрузке различными видами растительного материала.

The results of the investigation of the action of the microwave electromagnetic field on materials of plant origin for the purpose of determining optimal processing conditions in various technologies (seed biostimulation, heat treatment of a straw substratum, extraction of biologically active substances) are presented. The method of achieving this goal is a generalization of the calculated values for the heat of conversion of the microwave field energy when processing materials of different nature, with different moisture content and varying the loading of the microwave chamber. It is claimed that in order to obtain the effect of biostimulation, it is required to withstand the regime parameters at a level that does not allow the rupture of the cell walls, while in the preparation of the substrate this effect is preferable. When extracting biologically active substances (BAS), the development of pressure gradients in plant tissue helps to speed up the process, however, for every particular type of BAS, it is necessary to withstand the level of temperatures that can not damage the final product. The data on the optimal conditions for the microwave effect on a specific plant material for various technologies are obtained in the form of parameters such as the specific heat flux, the heating rate, and the processing time is obtained is presented. On the basis of the calculations, the curves of the efficiency of the chamber on the mass of the material being loaded are obtained. Analysis of the curves led to the conclusion that when processing the plant materials under study, the ratio of the volume of the chamber to the volume of the material should be no less than ten. The maximum value of efficiency is achieved for the material, which is humidificated according to technological conditions.
Study of efficiency of microwave processing of materials of plant origin
Keywords: микроволновое поле; растительная ткань; энергия; теплота; оптимальные параметры; коэффициент полезного действия; microwave field; plant tissue; optimal parameters